The Balkan War and Its Implications for Islamic Socio-Political Life in Southeast Europe (1876-1914 AD) - Antonella Belleza (International Journal of Science and Society, 2022)
This research describes the historical series of the occurrence of the Balkan Wars and their implications for Muslim life there. This study took up three main issues, namely (1) the causes of the Balkan Wars, (2) the chronology of the Balkan Wars, and (3) what are the implications of the Balkan Wars on the socio-political life of Islam in the South-East. Europe. The research method used in this thesis is the historical research method. 4 steps, namely (1) Heuristic, (2) Source Criticism/Verification, (3) Interpretation and (4) Historiography. Two approaches are used in this study, namely the political and sociological approaches. While the theory I use in this research is theory. Theory of conflict and social change. The research results that the authors obtained are as follows: chronologically, the Balkan War was preceded by the Macedonian problem which eventually served as an excuse to legitimize the war. Basically, the main cause of this Balkan War was due to ambition and personal grudge between the respective rulers of the Balkan countries and the Ottoman Empire. It is also carried by the decline of the sultanate, Russian domination, the Turkish-Italian war (1911-1912), the idea of nationalism, propaganda, the formation of the Balkan alliance and the failure of diplomacy. The outbreak of the Balkan War not only brought about geopolitical changes, but was also a humanitarian catastrophe for Muslims in the Balkans who, at that time, had to accept the fact that their situation was no longer the same as when it was ruled by Muslims because authority had passed to non-Muslims.